Bangladesh's judicial encounter with the 1951 Refugee Convention - Hossain, M (Refugee Studies Centre, University of Oxford, 2021)
Despite Bangladesh not having ratified the 1951 Refugee Convention, a number of recent court judgements indicate respect for elements of the Convention’s rulings.